2020
DOI: 10.2478/sgem-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Shear strength of compacted Chlef sand: effect of water content, fines content and others parameters

Abstract: This paper presents a laboratory study of the combined effect of the water content and fines content on the mechanical behaviour of Chlef sand in a medium dense state (RD = 65%) and dense state (RD = 80%). Several mechanical parameters were evaluated such as shear strength, cohesion and friction angle at different water content w = 0, 1, 2 and 3% and different fines content Fc = 0, 10, 20, 30 and 40%. The test results showed that the shear strength of Chlef sand decrease with the increase fines content Fc = 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, these equations do not consider the effect of water on the sand. The authors of previous studies have found that the more water there is in the soft ground, the lower the shear resistance is [23][24][25]. This fact shows that the shear resistance F 2 applied to a wheel on water-containing soft ground, such as the seabed, is smaller.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, these equations do not consider the effect of water on the sand. The authors of previous studies have found that the more water there is in the soft ground, the lower the shear resistance is [23][24][25]. This fact shows that the shear resistance F 2 applied to a wheel on water-containing soft ground, such as the seabed, is smaller.…”
Section: Methodsmentioning
confidence: 93%
“…Geotechnics 2024, 4, FOR PEER REVIEW the lower the shear resistance is [23][24][25]. This fact shows that the shear resistanc plied to a wheel on water-containing soft ground, such as the seabed, is smaller.…”
Section: Problems Of Scallop Measurement With Wheeled Robots On the S...mentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, leads to an increase in the shear strength. Some authors, [2,3,4,5,6] showed that the shear strength reduces with fines added. Other researchers [7,8] have shown that the shear strength of sand increases with the increase of the fines content.…”
Section: Introductionmentioning
confidence: 99%
“…(Sun et al, 2022) studied the shear strength of compacted bentonite and found that soil moisture content affected the shear strength of bentonite during aging, with a lower value occurring at a moisture content of 24%. (Bouri et al, 2020) conducted direct shear tests on sandy soils with varying densities and reported that moisture content significantly affected shear strength. In addition, the cohesion and the angle of internal friction decreased as the moisture content increased.…”
Section: Introductionmentioning
confidence: 99%